Meningioma 1 is indispensable for mixed lineage leukemia-rearranged acute myeloid leukemia - Sharma, Amit; Jyotsana, Nidhi; Gabdoulline, Razif; Heckl, Dirk; Kuchenbauer, Florian; Slany, Robert; Ganser, Arnold; Heuser, Michael (Haematologica, 2020)
Mixed lineage leukemia (MLL/KMT2A) rearrangements MLL-r) are one of the most frequent chromosomal aberrations in acute myeloid leukemia. We evaluated the function of Meningioma 1 (MN1), a co-factor of HOXA9 and MEIS1, in human and murine MLL-rearranged leukemia by CRISPR-Cas9 mediated deletion of MN1. MN1 was required for in vivo leukemogenicity of MLL positive murine and human leukemia cells. Loss of MN1 inhibited cell cycle and proliferation, promoted apoptosis and induced differentiation of MLL-rearranged cells. Expression analysis and chromatin immunoprecipitation with sequencing from previously reported data sets demonstrated that MN1 primarily maintains active transcription of HOXA9 and HOXA10, which are critical downstream genes of MLL, and their target genes like BCL2, MCL1 and Survivin. Treatment of MLL-rearranged primary leukemia cells with antiMN1 siRNA significantly reduced their clonogenic potential in contrast to normal CD34 - hematopoietic progenitor cells, suggesting a therapeutic window for MN1 targeting. In summary, our findings demonstrate that MN1 plays an essential role in MLL fusion leukemias and serve as a therapeutic target in MLL-rearranged acute myeloid leukemia.
CRIS-Team WoS Importer:2020-05-22